The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2527/jas.2015-9994
|View full text |Cite
|
Sign up to set email alerts
|

Hulled and hull-less barley grains with the genetic trait for low-phytic acid increased the apparent total-tract digestibility of phosphorus and calcium in diets for young swine1

Abstract: A 35-d experiment was conducted using 63 crossbred pigs (35 barrows and 28 gilts) with an initial average BW of 7.0 kg and age of 28 d to evaluate the efficacy of the low-phytic acid (LPA) genetic trait in hulled or hull-less barley in isocaloric diets. Hulled barleys were the normal barley (NB) cultivar Harrington and the near-isogenic LPA mutant 955 (M955) with P availabilities of 36 and 95%, respectively. Hull-less lines were produced by crossing NB and the LPA mutant 422 line with a hull-less line, produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Apart from causing physiologic deficiencies, this leads to increased P inputs in agricultural systems, as fed P passes through the animal without being internalised. It was shown that a reduction of the phytate content of fodder from 0.18% to 0.04% while maintaining P concentrations could lead to a decline in excreted P of approximately 75% (Veum and Raboy 2016).…”
mentioning
confidence: 99%
“…Apart from causing physiologic deficiencies, this leads to increased P inputs in agricultural systems, as fed P passes through the animal without being internalised. It was shown that a reduction of the phytate content of fodder from 0.18% to 0.04% while maintaining P concentrations could lead to a decline in excreted P of approximately 75% (Veum and Raboy 2016).…”
mentioning
confidence: 99%